Maqamat as Therapeutic Spirituality: A Hermeneutic and Positive Psychology Approach in a Modern Context - Tubagus Tsalasna Arzaqul Kirom; Muhammad Muslim Aljihaad (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2025)
This study discusses the concept of maqamat in classical Sufism literature and its implementation in the context of modern life. Maqamat, as spiritual stages that a salik goes through, have been systematically developed by classical Sufis such as al-Sarraj, al-Qusyairi, and al-Hujwiri. This research uses a qualitative approach with literature study method and hermeneutic analysis to reconstruct the meaning of maqamat contextually. The results show that the reinterpretation of maqamat with a philosophical hermeneutic approach enables the integration of classical spiritual values into modern urban life, including in the realm of professional, community, and psychological therapy. In addition, the integration of the maqamat concept with positive psychology demonstrates its transformative potential in the development of contemporary therapeutic spirituality. This research offers a model of maqamat implementation that is flexible, inclusive, and relevant to the challenges of modern times, and bridges the gap between the classical Islamic spiritual treasures and the spiritual needs of modern humans.